Visual Neuroprosthesis - Stimulation of Visual Cortical Centers in The Brain. Design of Non-Invasive Transcranial Stimulation of Functional Neurons - Lešták, Ján (Ceska a slovenska oftalmologie, 2024)
PURPOSE: The purpose of the article is to present the history and current status of visual cortical neuroprostheses, and to present a new method of stimulating intact visual cortex cells. METHODS: This paper contains an overview of the history and current status of visual cortex stimulation in severe visual impairment, but also highlights its shortcomings. These include mainly the stimulation of currently damaged cortical cells over a small area and, from a morphological point of view, possible damage to the stimulated neurons by the electrodes and their encapsulation by gliotic tissue. RESULTS: The paper also presents a proposal for a new technology of image processing and its transformation into a form of non-invasive transcranial stimulation of undamaged parts of the brain, which is protected by a national and international patent. CONCLUSION: The paper presents a comprehensive review of the current options for compensating for lost vision at the level of the cerebral cortex and a proposal for a new non-invasive method of stimulating the functional neurons of the visual cortex.
Keywords: Visual Cortex; mozek; zrak; poruchy zraku; visual neuroprosthesis; cortical visual centers; lidé; Vision Disorders; zrakové korové centrum; transcranial stimulation; neurony; Vision, Ocular; Humans; Neurons; Brain